(untitled) (Journal of Analytical Oncology, 2023)
Tailored nanocarriers have gained huge research focus for brain drug delivery, aimed at combating several neuro-oncological conditions, such as the glioblastoma. The progress of knowledge on the pathogenesis of glioblastoma has allowed identifying the major hurdles for efficient treatment, encompassing biological interfaces (blood-brain barrier and blood-brain tumor barrier), specificities of tumor microenvironment, as well as both bulk and glioma stem cell subpopulations. These findings provided new insights into the molecular basis of glioblastoma, being a strong driving force behind development of targeted nanomedicines in this area. Diversified nanoparticles have been designed to target glioblastoma surface markers, overexpressed receptors, aberrant genes and signaling pathways, in addition to contemplating barriers targeting strategies. Nanotechnologies claim important and unique features, including the versatility in promoting both passive and active drug targeting, making them excellent candidates for brain drug delivery and one of the most appealing to overcome the obstacles of the current glioblastoma treatment. In this short review, we will report the mechanisms of overcoming the blood-brain barrier as well as various studies relating to the applications of nanotechnologies as drug delivery carriers in glioblastoma treatment.